Prognostic value of left atrial reservoir strain and global work efficiency in medically managed secondary mitral regurgitation: a mediation analysis - Kangla Liao; Chunhua Mo; Li Liu; Bi Huang; Suxin Luo (Frontiers in Cardiovascular Medicine, 2026)
Aims Left atrial reservoir strain (LASr) and global work efficiency (GWE) have individually demonstrated prognostic value in secondary mitral regurgitation (SMR), but their interrelationship and combined utility remain unclear. We aimed to investigate the independent prognostic value of LASr and GWE, and to explore whether GWE plays a role in the LASr–mortality association in medically managed SMR patients. Methods and results This retrospective study included 399 patients with SMR (median age 70.0 years, 66.4% male) who were medically managed without valve intervention. LASr and GWE were measured using speckle-tracking echocardiography. Cox regression and mediation analyses were performed. During a median follow-up of 35.0 months, 103 deaths (25.8%) occurred. Both LASr (adjusted HR 0.891 per 1% increase, 95% CI 0.850–0.933, P < 0.001) and GWE (adjusted HR 0.920 per 1% increase, 95% CI 0.891–0.951, P < 0.001) independently predicted all-cause mortality. Exploratory mediation analysis showed that GWE statistically accounted for a portion of the LASr–mortality association, with an indirect effect of −0.183 (95% CI −0.305 to −0.112, P < 0.001) and a mediation proportion of 16.3%. Conclusion In medically managed SMR patients, both LASr and GWE independently predict all-cause mortality, and GWE statistically accounts for the relationship between LASr and mortality. These findings generate the hypothesis that left atrial dysfunction is statistically associated with impaired myocardial work efficiency, supporting the integrated assessment of both parameters for risk stratification across different SMR severity and phenotypes.